Juridis Analysis of Cancellation of Sale & Purchase Agreement by Heirs in Matter of Buyer/Seller Who Has Died - Aksan Tudoni; Akhmad Khisni; Amin Purnawan (Sultan Agung Notary Law Review, 2021)
PPJB land contains the rights and obligations of the parties who made it, so that if the matters that have been agreed in the deed of sale and purchase are violated or not fulfilled by the parties who made it then the parties are authorized to request cancellation in the agreement before the court. In practice, the sale and purchase agreement can be revoked by the heirs.  The purpose of this study; to find out how the position of the Heirs' Law and legal protection to the Buyer in the case of the Sale and Purchase Agreement entered into by the Heir is canceled by the heirs and How the Laws of the Cancellation of the Sale and Purchase Agreement are Unilateral by the Heirs. The method used in this study is the Sociological Juridical method, the specification in this study is descriptive analytical, the data used is primary and secondary data, using data collection with interviews and library studies, qualitative data analysis, problems analyzed with theory, legal certainty and Authority Theory. The results of this study show that, the heirs can cancel the sale and purchase of the heirs' land if the legal conditions of the sale and purchase are not met through the court. Heirs who do not give their consent in the sale and purchase of inherited land as their right, have the right to cancel the sale and purchase of the land. If an agreement does not meet the Subjective requirements, then the agreement can be revoked. The PPJB Deed made by the Notary is basically an authentic act that will not be disputed if one party does not feel harmed, but with the content of the agreement in PPJB then the cancellation can arise a problem because one party feels harmed by the other party.The seller who is the heir has an obligation to continue the agreement, because the heirs receive the obligation from the heirs in general, in the sense of assets and passions of the heirs are the responsibility of the heirs.